1992
DOI: 10.4269/ajtmh.1992.47.181
|View full text |Cite
|
Sign up to set email alerts
|

Vector Density Gradients and the Epidemiology of Urban Malaria in Dakar, Senegal

Abstract: The dispersion of anopheline mosquitoes from their breeding places and its impact on malaria epidemiology has been investigated in Dakar, Senegal, where malaria is hypoendemic and almost exclusively transmitted by Anopheles arabiensis. Pyrethrum spray collections were carried out along a 9 l0-meter area starting from a district bordering on a permanent marsh and continuing into the center of the city. According to the distance from the marsh, vector density (the number of An. arabiensis per 100 rooms) at 0-160, Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
172
1
5

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(187 citation statements)
references
References 2 publications
9
172
1
5
Order By: Relevance
“…En Quibdó, como en áreas urbanas de África, diversos factores podrían contribuir a la presencia de focos de malaria en zonas periurbanas, tales como la urbanización poco planeada, la deficiencia en la infraestructura de vivienda (10), la carencia de servicios públicos, el bajo nivel socioeconómico de la población que habita en los límites de la ciudad (11) y la cercanía de las casas a campos irrigados y en general a cuerpos de agua y territorios ricos en vegetación en donde posiblemente la disponibilidad de criaderos es mayor (12,13) . En contraste, las zonas altamente urbanizadas del centro de la ciudad con casas de concreto y sin vegetación presentan las incidencias más bajas y son negativas para criaderos (Freddy Córdoba, Programa de Control de Malaria Quibdó; comunicación personal) (11).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En Quibdó, como en áreas urbanas de África, diversos factores podrían contribuir a la presencia de focos de malaria en zonas periurbanas, tales como la urbanización poco planeada, la deficiencia en la infraestructura de vivienda (10), la carencia de servicios públicos, el bajo nivel socioeconómico de la población que habita en los límites de la ciudad (11) y la cercanía de las casas a campos irrigados y en general a cuerpos de agua y territorios ricos en vegetación en donde posiblemente la disponibilidad de criaderos es mayor (12,13) . En contraste, las zonas altamente urbanizadas del centro de la ciudad con casas de concreto y sin vegetación presentan las incidencias más bajas y son negativas para criaderos (Freddy Córdoba, Programa de Control de Malaria Quibdó; comunicación personal) (11).…”
Section: Discussionunclassified
“…De todos estos factores, la distancia de las viviendas a los criaderos se constituye en uno de los principales determinantes del riesgo de malaria en las áreas urbanas (12,(14)(15)(16), como lo ilustra un estudio en un área periurbana de Maputo, Mozambique, donde el riesgo de infección fue 6,2 veces más alto para las personas que vivían a menos de 200 metros de los criaderos comparado con los individuos que vivían a 500 metros o más (14). En nuestro caso no se tuvo información de la localización exacta de los criaderos para hacer este tipo de análisis.…”
Section: Discussionunclassified
“…Further avenues for the extension of host availability models are also suggested by equation [4], which outlines a simple model describing the known restriction of host dispersal (Gillies, 1961;Trape et al, 1992;Manga et al, 1993;Thompson et al, 1997), feeding cycle length Charlwood & Graves, 1987) and mortality rate (Charlwood, 1986) by host availability. This relationship is consistent with the observed dependence of adult dispersal upon the relative proximity of hosts and larval habitats (Edman et al, 1998) and the choice of oviposition sites in proximity to preferred hosts (Charlwood & Edoh, 1996;Minakawa et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Their occurrence has been attributed to several factors, including climatic anomaly, 2,4 land-use changes, 5 drug resistance, 3,6 population migration, 7 and breakdown of both the local health system and vector control activities. 8 Different authors have shown that Anopheles density, malaria transmission, and corresponding human infections were higher and clustered around the breeding sites, 9,10 particularly in the lowly endemic 11 and epidemic-prone areas. 12 Highlands' hilly slopes 13 and cold nights 14 limit upward dispersal of adult mosquitoes from the valleys, accentuating their clustering.…”
Section: Introductionmentioning
confidence: 99%